History Undercover: Last Mass Execution - Constantine, Craig (Towers Productions Inc., 1997)
Duration: 00:50:00 In August, 1945, seven German prisoners of war were hanged at Fort Leavenworth, Kansas. The prisoners did not commit a crime against the United States--they murdered one of their own, German U-boat crewmember, Werner Drechsler. He cooperated with U.S. Naval Intelligence for the interrogation of other German POWs. His fellow POWs demanded retribution for his betrayal to themselves and Germany. When transferred to Fort Leavenworth after his cooperation, authorities put Drechsler into the general population with his former comrades, his former comrades recognized him and passed judgement. They murdered Drechsler on his first night in Fort Leavenworth.